1991
DOI: 10.1128/iai.59.10.3366-3371.1991
|View full text |Cite
|
Sign up to set email alerts
|

Surface structures and adherence properties of diverse strains of Haemophilus influenzae biogroup aegyptius

Abstract: Haemophilus influenzae biogroup aegyptius is an important cause of conjunctivitis and has recently been associated with Brazilian purpuric fever (BPF), a fulminant systemic disease of children. To gain insight into the bacterial factors involved in the pathogenesis of this disease, we investigated the surface structures and adherence properties of eight different strains of H. influenzae biogroup aegyptius, including both BPF and non-BPF isolates. All eight strains were able to express long peritrichous pili s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Because of the similarity of HadA to TAAs, we investigated its ability to mediate in vitro bacterial adherence and invasion of Chang epithelial cells (human conjunctival cells), which represent an in vitro model to study infection of H. influenzae biogroup aegyptius (St Geme et al, 1991;Farley et al, 1992). In accordance with previous observations (Li et al, 2003), we found H. influenzae biogroup aegyptius strains resistant to genetic manipulation, and our attempts to construct an isogenic BPF hadA mutant were unsuccessful, also following a previously described method (Segada and Lesse, 1997).…”
Section: Hada Mediates Bacterial Adhesion Invasion and Microcolony Fmentioning
confidence: 60%
See 2 more Smart Citations
“…Because of the similarity of HadA to TAAs, we investigated its ability to mediate in vitro bacterial adherence and invasion of Chang epithelial cells (human conjunctival cells), which represent an in vitro model to study infection of H. influenzae biogroup aegyptius (St Geme et al, 1991;Farley et al, 1992). In accordance with previous observations (Li et al, 2003), we found H. influenzae biogroup aegyptius strains resistant to genetic manipulation, and our attempts to construct an isogenic BPF hadA mutant were unsuccessful, also following a previously described method (Segada and Lesse, 1997).…”
Section: Hada Mediates Bacterial Adhesion Invasion and Microcolony Fmentioning
confidence: 60%
“…Enhanced attachment to conjunctival cells was demonstrated for BPF clone strain F3031 compared with that of a non-BPF strain, but the reason for this difference remains unknown (Farley et al, 1992). Moreover, in vitro adherence of H. influenzae biogroup aegyptius to conjunctival cells occurred independently of the presence of long pili detected in some strains (St Geme et al, 1991) and of the Hap protein, which is not expressed in BPF clone strains (Kilian et al, 2002), suggesting that other adhesive factors have to be present on the bacterial surface.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies reported by Qui et al (1998) indicated that human lactoferrin is capable of abolishing Hap-mediated adherence of H. influenzae. It is possible that lack of this target for lactoferrin is an advantage for strains of H. aegyptius and H. influenzae biogroup aegyptius, which may have compensated by enhanced expression of surface pili (Weyant et al, 1990;Reid et al, 1996) or other non-pilus adhesin (St Geme et al, 1991). Feavers and Maiden (1998) recently proposed that the loss of expression of porA was one of the steps in the emergence of the gonococcus from a population that is represented today by the meningococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a number of phenotypic differences have been demonstrated including an elongated rod shape of H. aegyptius (Pittman and Davis, 1950;Mazloum et al ., 1982), and the two taxa seem to differ with respect to pathogenic potential, although systematic evidence for this assumption is lacking. Since the discovery of BPF, H. influenzae biogroup aegyptius and H. aegyptius have often been treated as synonyms because of their mutual association with conjunctivitis, and the fact that they share a number of phenotypic traits (urease activity, inability to ferment xylose, lack of indole production, and lack of ornithine decarboxylase activity) (Brenner et al ., 1988;Musser and Selander, 1990;St Geme et al ., 1991). However, there is no direct genetic evidence to support the assumption that they are indistinguishable.…”
Section: Introductionmentioning
confidence: 99%